Seroprevalence as an Indicator of Undercounting of COVID-19 Cases in a Large Well-Described Cohort - Kevin M. Taylor, MD; Keersten M. Ricks, PhD; Paul A. Kuehnert, MS; Angelia A. Eick-Cost, PhD; Mark R. Scheckelhoff, PhD; Andrew R. Wiesen, MD; Tamara L. Clements, MS; Zheng Hu, MS; Samantha E. Zak, MS; Scott P. Olschner, BS; Andrew S. Herbert, PhD; Sara L. Bazaco, PhD; et al. (Elsevier, 2023)
Introduction: Reported confirmed cases represent a small portion of overall true cases for many infectious diseases. The undercounting of true cases can be considerable when a significant portion of infected individuals are asymptomatic or minimally symptomatic, as is the case with COVID-19. Seroprevalence studies are an efficient way to assess the extent to which true cases are undercounted during a large-scale outbreak and can inform efforts to improve case identification and reporting. Methods: A longitudinal seroprevalence study of active duty U.S. military members was conducted from May 2020 through June 2021. A random selection of service member serum samples submitted to the Department of Defense Serum Repository was analyzed for the presence of antibodies reactive to SARS-CoV-2. The monthly seroprevalence rates were compared with those of cumulative confirmed cases reported during the study period. Results: Seroprevalence was 2.3% in May 2020 and increased to 74.0% by June 2021. The estimated true case count based on seroprevalence was 9.3 times greater than monthly reported cases at the beginning of the study period and fell to 1.7 by the end of the study. Conclusions: In our sample, confirmed case counts significantly underestimated true cases of COVID-19. The increased availability of testing over the study period and enhanced efforts to detect asymptomatic and minimally symptomatic cases likely contributed to the fall in the seroprevalence to reported case ratio.